Improvement of the Competence and Affective Disposition of Junior High School Teachers After the Implementation of Biodiversity Literacy Textbooks Containing Material on the Local Potency of West Java - Nuraeni, Hasna; Rustaman, Nuryani; ., Saefudin; Hidayat, Topik (KnE Social Sciences, 2024)
This study aimed to analyze the improvement of competence and affective disposition of junior high school teachers after implementing biodiversity literacy textbooks containing material on the local potency of West Java. The study used a weak experimental design with the one group pretest post-test method. A total of 33 junior high school teachers from various districts in West Java Province were involved in the research conducted from January 2020 to August 2021. The results showed that there was an average increase in competence (71%) and affective disposition (69%) of biodiversity literacy. There was a sequential increase in biodiversity literacy competence, namely, scientifically explaining biodiversity phenomena (77%), evaluating scientific inquiry related to biodiversity (74%), scientific interpretation of biodiversity data and evidence (73%), and designing scientific inquiries related to biodiversity (68%). There was an increase in the level of biodiversity literacy competence at level 4 (21%), level 5 (15%), and level 6 (48%). There was an increase in affective disposition in the form of sensitivity and positive values (88%), self-confidence, personal and social responsibility (69%), interest (68%), and concern for biodiversity (67%). The results of hypothesis testing with the Wilcoxon Test resulted in a sig value of 0.000 for competence and attitude disposition. The study concluded that biodiversity literacy textbooks containing material on the local potency of West Java can help improve the competence and affective disposition of biodiversity literacy of junior high school teachers. Keywords: competence, affective disposition, biodiversity literacy, local potency, West Java